Enantiopure titanocene complexes: direct evidence for paraptosis in cancer cells - Cini, Melchior; Williams, Huw Edward Llewelyn; Fay, Mike W.; Searle, Mark; Woodward, Simon; Bradshaw, Tracey D. (Royal Society of Chemistry, 2016)
Tolerated by normal tissues, anti-cancer therapies based on titanium compounds are limited by low efficacy/selectivity and lack of understanding of their mode(s) of action. In vitro antitumour activity and mode of cell death incurred by enantiopure TiCl2{n-C5H4CHEt(2 MeOPh)}2 (abbreviated CpR 2TiCl2) has been investigated. The in vitro anti-tumour activity of CpR 2TiCl2 is selective for cancer cells; in clonogenic assays, (S,S)-CpR 2TiCl2 was twice as effective at inhibiting colony formation than other stereoisomers after 24 h exposure. HPLC, MS and NMR techniques determined hydrolysis of CpR 2TiCl2; data strongly correlate with soluble [CpR 2Ti(OH (OH2)]+ being the biological trigger. Treatment of cells with CpR 2TiCl2 provoked extensive cytoplasmic vacuolization, endoplasmic reticulum (ER) swelling and activation of MAPKinase signal transduction, consistent with ligand-induced paraptosis, type III cell death, which is morphologically distinct from, and independent of apoptosis. Indeed, distinct from cisplatin, CpR 2TiCl2 failed to perturb cell cycle dynamics, induce γH2AX foci or evoke apoptosis in MDA-MB-468 and HCT-116 cells.